Gamification Group Counseling to Enhance Academic Resilience among Students with Learning Disabilities: The Mediating Role of Academic Self-Efficacy - A. Muh Ramadhan AS; Wahyu Nurhamzah; Rustinah Rustinah; Muhammad Ilham Bakhtiar (Indonesian Journal of Learning Education and Counseling, 2025)
This study aims to test the effectiveness of a group counseling intervention based on gamification, joyful learning, in improving the academic resilience of students with learning disabilities and to analyze the role of academic self-efficacy as a mediating variable in this relationship. The study used a quantitative approach with a quasi-experimental design (pretest-posttest control group design). It involved 60 junior high school students selected using a purposive sampling technique, consisting of 30 students in the experimental group and 30 students in the control group. Data were collected using academic self-efficacy and academic resilience scales that had undergone validity and reliability tests. Data analysis was conducted using SEM-PLS. The results showed that the structural model had good explanatory capabilities in explaining the relationship between variables. Joyful learning proved to be the most dominant factor in improving students' academic resilience. Counselor competence also had a positive and significant effect on academic resilience, although it did not have a significant direct effect on the development of learning independence (self-learning development). In addition, academic resilience showed a positive but not yet significant effect on self-learning development. Findings indicate that enjoyable, meaningful, and participatory learning experiences play an important role in strengthening the academic resilience of students with learning disabilities.